Distribution and resistance of pathogens in liver transplant recipients with Acinetobacter baumannii infection - Gao F; Ye QF; Wan QQ; Liu S; Zhou JD (Dove Medical Press, 2015)
Fei Gao,1 Qifa Ye,2,3 Qiquan Wan,2 Shan Liu,4 Jiandang Zhou51Infectious Disease Department of Henan Province People’s Hospital, Zhengzhou, 2Department of Transplant Surgery, Third Xiangya Hospital, Central South University, Changsha, 3Department of Transplant Surgery, Zhongnan Hospital, Wuhan University, Wuhan, People’s Republic of China; 4Adelphi University College of Nursing and Public Health, New York, NY, USA; 5Department of Clinical Laboratory of Microbiology, Third Xiangya Hospital, Central South University, Changsha, People’s Republic of ChinaBackground: Drug-resistant Acinetobacter baumannii has become a major problem in liver transplant recipients. The aim of this study was to investigate the clinical presentation, distribution, and drug susceptibility characteristics in liver recipients with A. baumannii infection.Methods: We retrospectively investigated 17 liver recipients who developed A. baumannii infection between January 1, 2007 and December 31, 2014. The distribution of A. baumannii and drug susceptibility characteristics were reviewed.Results: Infectious complications due to A. baumannii appeared in 17 liver recipients, with a total of 24 episodes. Approximately 63% (15/24) of A. baumannii infections occurred within 2 weeks after transplantation. The most common source of infection was multiple culture-positive sites (35.3%, n=6), followed by the intra-abdominal/biliary tract (23.5%, n=4) and lung (23.5%, n=4). Eight patients (47.1%) had a body temperature of 38°C or higher at the onset of A. baumannii infection. Nine, seven, and 12 recipients had a serum creatinine level of >1.5 mg/dL, a white blood cell count of >15,000/mm3, and a platelet count of <50,000/mm3, respectively. There were five (29.4%) cases of septic shock and eight (47.1%) deaths. The rate of antibiotic resistance of A. baumannii to ten of 12 antibiotics investigated was more than 60%. Among the 24 infections caused by A. baumannii, 75% were carbapenem-resistant. The rods were relatively sensitive to tigecycline and cefoperazone-sulbactam.Conclusion: The clinical manifestations of A. baumannii infection included a high body temperature, a decreased platelet count, an elevated white blood cell count, and onset in the early period after transplantation as well as high mortality. The antibiotic resistance rate of A. baumannii was extremely high. Prevention measures and combination antibiotic therapy are needed to improve the outcomes of liver recipients with A. baumannii infections.Keywords: liver transplantation, Acinetobacter baumannii, infections, manifestation, drug resistance